Geomorphology and InSAR-Tracked Surface Displacements in an Ice-Rich Yedoma Landscape - van Huissteden, J.; Teshebaeva, K.; Cheung, Y.; Magnússon, R. Í.; Noorbergen, H.; Karsanaev, S. V.; Maximov, T. C.; Dolman, A. J. (Frontiers in Earth Science, 2021)
Ice-ridge Yedoma terrain is susceptible to vertical surface displacements by thaw and refreeze of ground ice, and geomorphological processes of mass wasting, erosion and sedimentation. We explore the relation between a three year data set of InSAR measurements of vertical surface displacements during the thaw season, and geomorphological features in an area in the Indigirka Lowlands, Northeast Siberia. The geomorphology is presented in a map, based on interpretation of high resolution satellite imagery, field surveys and data from paleo-environmental research. The main landforms comprise overlapping drained thaw lake basins and lakes, erosion remnants of Late Pleistocene Yedoma deposits, and a floodplain of a high-sinuosity anastomosing river with ancient river terrace remnants. The spatial distribution of drained thaw lake basins and Yedoma erosion remnants in the study area and is influenced by neotectonic movements. The three years of InSAR measurement include two years of high snowfall and extreme river flooding (2017-2018) and one year of modest snowfall, early spring and warm summer (2019). The magnitude of surface displacements varies among the years, and show considerable spatial variation. Distinct spatial clusters of displacement trajectories can be discerned, which relate to geomorphological processes and ground ice conditions. Strong subsidence occurred in particular in 2019. In the wet year 2017, marked heave occurred at Yedoma plateau surfaces, likely by ice accumulation at the top of the permafrost driven by excess precipitation. The spatial variability of surface displacements is high. This is explored by statistical analysis, and is attributed to the interaction of various processes. Next to ground ice volume change, also sedimentation (peat, colluvial deposition) and shrinkage or swelling of soils with changing water content may have contributed. Tussock tundra areas covered by the extreme 2017 and 2018 spring floods show high subsidence rates and an increase of midsummer thaw depths. We hypothesize that increased flood heights along Siberian lowland rivers potentially induce deeper thaw and subsidence on floodplain margins, and also lowers the drainage thresholds of thaw lakes. Both mechanisms tend to increase floodplain area. This may increase CH4 emission from floodplains, but also may enhance carbon storage in floodplain sedimentary environments.